Difference in structural and chemical properties of sol-gel spn coated Al doped TiO2, Y doped TiO2 and Gd doped TiO2 based on trivalent dopants - Mohd Said, Nor Damsyik; Sahdan, Mohd Zainizan; Nayan, Nafarizal; Saim, Hashim; Adriyanto, Feri; Bakri, Anis Suhaili; Morsin, Marlia (The Royal Society of Chemistry, 2018)
n this research, pure titanium dioxide (TiO2) and doped TiO2 thin film layers were prepared using the spin coating method of titanium(IV) butoxide on a glass substrate from the sol–gel method and annealed at 500 °C. The effects on the structural and chemical properties of these thin films were then investigated. The metal doped TiO2 thin film which exists as trivalent electrons consists of aluminium (Al), yttrium (Y) and gadolinium (Gd). The anatase phase of the thin films was observed and it was found that the crystal size became smaller when the concentration of thin film increased. The grain size was found to be 0.487 to 13.925 nm. The types of surface morphologies of the thin films were nanoporous, with a little agglomeration and smaller nanoparticles corresponding to Al doped TiO2, Y doped TiO2 and Gd doped TiO2, respectively. The trivalent doping concentration of the thin films increased with a rising of thickness of the thin film. This can contribute to the defects that give advantages to the thin film when the mobility of the hole carriers is high and the electrons of Ti can move easily. Thus, Ti3+ existed as a defect state in the metal doped TiO2 thin film based on lattice distortion with a faster growth thin film that encouraged the formation of a higher level of oxygen vacancy defects.